Exploiting Peptide Self-Assembly for the Development of Minimalistic Viral Mimetics - Janković, Patrizia; Šantek, Iva; Pina, Ana Sofia; Kalafatovic, Daniela (Frontiers in Chemistry, 2021)
Viruses are natural supramolecular nanostructures that form spontaneously by molecular self-assembly of complex biomolecules. Peptide self-assembly is a versatile tool that allows mimicking viruses by creating their simplified versions through the design of functional, supramolecular materials with modularity, tunability, and responsiveness to chemical and physical stimuli. The main challenge in the design and fabrication of peptide materials is related to the precise control between the peptide sequence and its resulting supramolecular morphology. We provide an overview of existing sequence patterns employed for the development of spherical and fibrillar peptide assemblies that can act as viral mimetics, offering the opportunity to tackle the challenges of the ongoing pandemic, as well as viral infections in general.